2015
DOI: 10.1016/j.fob.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species induce Cox‐2 expression via TAK1 activation in synovial fibroblast cells

Abstract: HighlightsOxidative stress in the arthritis joint is involved in generating mediators for inflammation.Oxidative stress-induced expression of Cox-2 was mediated by MAPKs and NF-κB.ROS-induced MAPKs and NF-κB were attenuated by inhibition of MAPKKK TAK1.Inhibition of TAK1 activity resulted in reduced expression of Cox-2 and PGE2.ROS-induced TAK1 activation and Cox-2 expression was inhibited by antioxidants N-acetyl cysteamine and hyaluronic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(76 citation statements)
references
References 64 publications
2
73
1
Order By: Relevance
“…36 In addition, research has also suggested that oxidative stress induced phosphorylation of MAPKs and NF-κB through TAK1 activation can result in increased COX-2. 37 From these results, we conclude that oxidative stress is an important factor for generating COX-2.…”
Section: Effects On Mapks Activitymentioning
confidence: 76%
“…36 In addition, research has also suggested that oxidative stress induced phosphorylation of MAPKs and NF-κB through TAK1 activation can result in increased COX-2. 37 From these results, we conclude that oxidative stress is an important factor for generating COX-2.…”
Section: Effects On Mapks Activitymentioning
confidence: 76%
“…In that study, the FFA4-β-arrestin-2 axis was responsible for sequestration of TAB1 by β-arrestin-2, blocking the TAB1/TAK1 interaction that facilitates NF-κB activity (13). The ability of FFA4-β-arrestin-2 signaling to inhibit TAK1 effects are also of note given the importance of TAK1 in ROS-dependent upregulation of COX-2 (5), signifying that the noted effects of FFA4 on ROS generation may also be mediated, at least in part, by β-arrestin-2, a hypothesis that is confirmed by reduced ability of FFA4-S–Δ340 to decrease ROS generation. However, a curiosity of these data is the lack of effect of FFA4-L-WT, the purported β-arrestin-biased isoform, on inhibition of NF-κB activity, since neither FFA4-L-WT or FFA4-L–Δ356 were able to reduce LPS-mediated NF-κB or ERK1/2 activities, contrary to their ability to reduce PMA-mediated ROS generation.…”
Section: Discussionmentioning
confidence: 94%
“…Since ROS are known to play a part in increasing expression of pro-inflammatory COX-2 in macrophages and other cell types (58), we next assessed the role of FFA4 in modulating COX-2 expression. In untransfected Raw 264.7 macrophages, PMA treatment (1 μM, 4 h) induced COX-2 expression via PKC, as BIMII (10 μM 1 h prior to PMA) completely abolished the effect (Fig 6A).…”
Section: Resultsmentioning
confidence: 99%
“…Reduction of ROS can inhibit inflammation in the RA joint, with studies showing that ROS scavengers can reduce oxidative stress in RASFs and can significantly decrease osteoclastogenesis and proinflammatory cytokines in mouse models of arthritis . In addition, ROS induces cyclooxygenase 2 and the key MAPK, NF‐κB, and transforming growth factor β–activated kinase signaling pathways in RASFs , and coculture of RASFs with peripheral blood mononuclear cells increases the number of CD4+CXCR5+ inducible costimulator–positive T cells, an effect mediated in part by increased ROS .…”
Section: Discussionmentioning
confidence: 99%